The Energetics of a Three‐State Protein Folding System Probed by High‐Pressure Relaxation Dispersion NMR Spectroscopy. Issue 38 (14th September 2015) - Tugarinov, Vitali; Libich, David S.; Meyer, Virginia; Roche, Julien; Clore, G. Marius
Abstract The energetic and volumetric properties of a three‐state protein folding system, comprising a metastable triple mutant of the Fyn SH3 domain, have been investigated using pressure‐dependent 15N‐relaxation dispersion NMR from 1 to 2500 bar. Changes in partial molar volumes (ΔV) and isothermal compressibilities (ΔκT) between all the states along the folding pathway have been determined to reasonable accuracy. The partial volume and isothermal compressibility of the folded state are 100 mL mol−1 and 40 μL mol−1 bar−1, respectively, higher than those of the unfolded ensemble. Of particular interest are the findings related to the energetic and volumetric properties of the on‐pathway folding intermediate. While the latter is energetically close to the unfolded state, its volumetric properties are similar to those of the folded protein. The compressibility of the intermediate is larger than that of the folded state reflecting the less rigid nature of the former relative to the latter.